A new approach to the synthesis of trinuclear gold(i) imidazolate complexes and their silver(i)-induced photoluminescence behavior. Issue 20 (29th April 2020) - Ruiz, Javier; Sol, Daniel; Mateo, María A.; Vivanco, Marilín; Badía-Laiño, Rosana
Abstract : Triangular gold(i ) N -arylimidazolate clusters have been prepared by a pNHC metalation protocol and their photoluminescence has been switched on by the addition of Ag + . Abstract : New trinuclear gold(i ) N -arylimidazolate cluster complexes have been synthesized from cationic [Au(CNR)2 ] + isocyanide complexes and their structure and photoluminescence behavior have been compared with those of their 1-methylimidazolate counterpart. A drastic change in their photophysical properties was observed upon coordination of the Ag + cation.